Host–guest-driven color change in water: influence of cyclodextrin on the structure of a copper complex of poly((4-hydroxy-3-(pyridin-3-yldiazenyl)phenethyl)methacrylamide-co-dimethylacrylamide) - Retzmann, Nils; Maatz, Gero; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2014)
In the present work we report the synthesis of poly((4-hydroxy-3-(pyridin-3-yldiazenyl)phenethyl)methacrylamide-co-dimethylacrylamide) and its reversible optical and complex-forming properties due to copper and cyclodextrin (CD) interactions. Color changing effects are characterized by UV–vis spectroscopy and the supramolecular behavior is investigated by dynamic light scattering experiments.
Keywords: cyclodextrin; copolymer; copper(II) sulfate; supramolecular; water complex